Strategy Implementation and Media Promotion Training for the Mangrove Tourism Park in Jenggalu Kito Village, Bengkulu City - Fiona, Febzi; Praningrum, Praningrum; Pareke, Fachrudin JS; Nasution, Nasution; Hadi, Effed Darta (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
Bengkulu City iscoastal areas that have a lot of tourism potential, one of which is Kampung Jenggalu Kito. This tourist area has not been promoted optimally, this can be seennot maximal efforts to develop mangrove tourism inJenggalu Kito Village, becauseThere is no effective promotional media. This causes the development of tourist areas has not been carried out optimally. Based on these conditions, it is necessary to provide training on the implementation of tourism promotion strategies and media for the community and related officials as executors.The purpose of this activity isprovide an understanding to the public of the importance of strategy and promotional media as a means to increase tourism potential, and introduce various promotional strategies and promotional media both print and electronic for the development of mangrove tourism inJenggalu Kito village, Bengkulu city. From the results of this dedication, several strategies were found that could be carried out for the promotion of mangrove tourism in Jenggalu Kito Village, namely by: identifying tourism products, formulating the advantages of tourism products, setting market targets, setting visit prices